Characterization of Functional Groups in Sengon Biochar Under Various Pyrolysis Temperatures: Karakterisasi Gugus-Gugus Fungsional Biochar Sengon pada Perlakuan Berbagai Suhu Pirolisis - NADA SALSABILA PRADHANI; DJOKO MULYANTO (Universitas Pembangunan Nasional Veteran Yogyakarta, 2025)
The decline in soil quality due to pollution and the depletion of nutrients can be addressed by using biochar as a soil conditioner. This study utilized sengon biochar pyrolyzed at temperatures of 300°C, 500°C, and 700°C to analyze differences in functional group characteristics and their ability to adsorb ions. The objective of this study was to identify the functional groups of biochar at various pyrolysis temperatures and to determine the optimal temperature for enhancing the soil's ion adsorption capacity. The methods employed included functional group characterization using FTIR and ion adsorption testing using gentian violet and eosin red dyes. The results showed that biochar at 300°C retained dominant hydroxyl (-OH) and carbonyl (C=O) functional groups. Biochar at 500°C exhibited increased aromatic structure with dominant aromatic C=C groups while still retaining hydroxyl groups. Biochar at a pyrolysis temperature of 700°C loses many functional groups and is dominated by aromatic carbon. The best ion adsorption capacity is found in biochar at 500°C, followed by biochar at 700°C, and finally biochar at 300°C. Keywords: Analysis, organic materials, adsorption, ion. Keywords: Analysis, Organic Matter, Adsorption, Ion